Discourse of Socio-Cultural Realities in the Situation of Civilization Transformations in Modern Ukraine - Kolieva, Iryna (Київський національний університет імені Тараса Шевченка, 2016)
The article deals with the philosophical comprehension of the cultural phenomena in modern Ukraine. It is pointed out that the spiritual life of the individual is an integral part of the spiritual life of the society. Both the positive achievements of the modern Ukrainian culture in literature, cinema, social life aa well as the negative factors preventing the fruitful development of the cultural life of the country are also analyzed.Keywords: Culture, Spirituality, Uniqueness, Society, Personality, History.

Ірина КолієваФілософське осмислення культурних реалій розглядається в умовах сьогоденної України. Зазначається, що духовне життя особистості є невід’ємним складником духовного життя суспільства. Аналізуються як позитивні надбання сучасної української культури у сфері літератури, кіномистецтва, суспільного життя, так і негативні чинники, що перешкоджають плідному розвитку культурного життя країни.Ключові слова: культура, духовність, самобутність, суспільство, особистість, історія.
Дискурс соціокультурних реалій в умовах цивілізаційних трансформацій у сучасній Україні